EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
As the new chief editor of the Journal of Research, Policy & Practice of Teachers & Teacher Education (JRPPTTE), I hope to continue to improve the content and increase the readership of this journal. Emeritus Professor Nagendralingan Ratnavadivel, the outgoing chief editor and the journal’s founding editor, has left me with a very tough act to follow. There is no way that I can hope to match the incredible development and expansion he has made to the quality of the journal since 2012. I hope to fill his shoes in maintaining JRPPTTE as a quality publication that is responsive to the needs of its readers and contributors. Thank you Emeritus Professor Nagendralingan Ratnavadivel for your expertise and contribution. You will always be a part of this journal.